Model for the evaluation of implementation programs and professional pharmacy services - Moullin, Joanna; Sabater-Hernández, D.; Benrimoj, S. (Elsevier, 2016)
© 2016 Elsevier Inc. Pharmacy practice and pharmaceutical care research of professional services has largely focused on patient outcomes and cost-effectiveness. Research studies have been, for the most part, conducted in controlled conditions prior to full scale implementation. There appears to be a dearth of process and evaluation of implementation reported. Conducting implementation research or adding implementation measures to an impact study, adds external validity to service and patient outcomes. Evaluations are required for all aspects of implementation including indicators of movement through the implementation stages (formative and summative implementation process evaluation), measures of influencing factors (barriers and facilitators) and change in factors over time (implementation impact), assessment of strategies and/or the implementation program, and overall measures to generate a level of implementation (implementation outcomes). The level of implementation of a professional pharmacy service can be estimated from the level of service delivery (reach and fidelity) and level as a service provider (integration and strength of support in the service environment). The model may be used for evaluating professional pharmacy services and for evaluating implementation programs.